Associations between aerobic exercise, muscle strength training and the prevalence of shoulder pain in manual wheelchair users with spinal cord injury - Wiebe H. K. De Vries; Ursina Arnet; Fransiska M. Bossuyt; Sonja de Groot; Inge Eriks-Hoogland; Claudio Perret (Bern Open Publishing, 2024)
Introduction The primary objective of this study is to explore associations between meeting spinal cord injury (SCI)-specific exercise guidelines and the prevalence of shoulder pain in manual wheelchair users (MWU) with SCI in Switzerland. The rationale behind this investigation lies in the high prevalence of shoulder pain among MWU with SCI, impacting their daily activities, leisure- and labor participation, and overall quality of life. Understanding the association between exercise adherence and shoulder pain is crucial, not only for the well-being of the individuals but also for managing healthcare costs associated with pain treatments. Methods The study utilizes data from the SwiSCI Community Survey 2022 (Gross-Hemmi et al., 2021), focusing on a cohort of 593 manual wheelchair users (MWU) for a cross-sectional analysis, investigating the reporting of shoulder pain, and adherence to SCI-specific exercise guidelines (Martin Ginis et al., 2018). The guidelines, proposed by Martin-Ginis et al. (2018), encompass aerobic exercise and muscle-specific strength training. Logistic regression analyses were employed to assess the association of meeting these guidelines and the prevalence of shoulder pain, while considering potential confounding factors. Results High prevalence of shoulder pain was observed, affecting 40% of the MWU surveyed, which is in line with previous observations. Additionally, the study found that a significant proportion of the population did not meet the recommended guidelines for aerobic exercise (46%) and muscle strength training (64%). Logistic regression analyses showed that non-adherence to aerobic exercise guidelines was associated with 1.55 to 1.97 higher odds of reporting shoulder pain. No association of muscle strength training with the shoulder pain could be found. Therefore, meeting both aerobic and muscle strength guidelines did not yield any association with shoulder pain. Adjustments for potential confounders such as sex, age, lesion level, completeness, time since injury, and mobility scores, did not change the association between adherence to guidelines and shoulder pain. Discussion/Conclusion The prevalence of shoulder pain in the study sample is high (40%) and in line with previous publications. Compared to 75% of the Swiss general population being physical active for more than 2.5 hour a week (Bundesamt für Statistik, 2019), only 54% of the study sample is meeting the guidelines for at least the "Starter level" on aerobic exercise (cardiorespiratory, ≥ 2x 20 min/week). Those who are not meeting the aerobic exercise guidelines have 1.55 to 1.97 higher odds to have shoulder pain. Despite foreseen shoulder fitness benefit, 64% is not meeting the guidelines on muscle strength training. To further examine the relation between shoulder use, -exercise and shoulder pain, longitudinal studies on dose-effect are needed. References Gross-Hemmi, M. H., Gemperli, A., Fekete, C., Brach, M., Schwegler, U., & Stucki, G. (2021). Methodology and study population of the second Swiss national community survey of functioning after spinal cord injury. Spinal Cord, 59, 363-372. https://doi.org/10.1038/s41393-020-00584-3 Martin Ginis, K. A., van der Scheer, J. W., Latimer-Cheung, A. E., Barrow, A., Bourne, C., Carruthers, P., Bernardi, M., Ditor, D. S., Gaudet, S., de Groot, S., Hayes, K. C., Hicks, A. L., Leicht, C. A., Lexell, J., Macaluso, S., Manns, P. J., McBride, C. B., Noonan, V. K., Pomerleau, P. ... Goosey-Tolfrey, V. L. (2018). Evidence-based scientific exercise guidelines for adults with spinal cord injury: an update and a new guideline. Spinal Cord, 56(4), 308-321. https://doi.org/10.1038/s41393-017-0017-3 Bundesamt für Statistik. (Ed.). (2019). Schweizerische Gesundheitsbefragung 2017. Körperliche Aktivität und Gesundheit [Swiss Health Survey 2017: Physical activity and health]. Bundesamt für Statistik. https://www.sportobs.ch/inhalte/Downloads/213-1708.pdf